Magnetismo de ferritas nanoestruturadas preparadas por mecanossíntese e Sol-Gel Protéico - Segatto, Breno Rodrigues (2011)
Magnetic properties of nanocrystalline AFe2O4 (A = Ni, Zn and Co) spinel-like mechanically processed and also of the nanocrystalline NiFe2O4 ferrite prepared by sol-gel technique have systematically been studied using temperature dependent from zero-field 57Fe Mössbauer spectrometry and magnetization measurements, while the crystal structures were investigated by X-ray difraction. Specifically, for the NiFe2O4mechanically processed in-field 57Fe Mössbauer spectrometry has also been performed. For the nanocrystalline ferrite mechanically processed with spinel-like, the hyperfine structure studied by Mössbauer spectroscopy allows us to distinguish two main magnetic contributions: one attributed to the crystalline grain core (n-G), which has magnetic properties similar to the bulk AFe2O4 (A = Ni, Zn and Co) spinel-like structure (n-AFe2O4) and the other one due to the disordered grain boundary region (GB), which presents topological and chemical disorder features (d-AFe2O4). Mössbauer spectrometry determines a large fraction for the d-AFe2O4 region of the nanocrystalline AFe2O4 ferrite milled for long times (longer than 80 hours). Under applied magnetic field, from Mössbauer it is determined that the n-NiFe2O4 spins are canted with angle dependent on the applied field magnitude, whereas a speromagnet-like structure is suggested for the d-NiFe2O4 with 63% of the Mossbauer spectra area. Mossbauer data for the nanocrystalline NiFe2O4 also show that even under 12 T no magnetic saturation is observed for the two magnetic phases (n-NiFe2O4 and d-NiFe2O4). In general, hysteresis loops for the AFe2O4 (A = Ni, Zn and Co), obtained in field cooling protocol and recorded for scan field (maximum field of 7 T), are shifted in both field and magnetization axes, for temperatures below about 50 K. It has also been shown that the spin configuration of the spin-glass-like phase of the NiFe2O4 ferrite is strongly modified by the consecutive field cycles, consequently the n-NiFe2O4/d- XIII NiFe2O4 magnetic interaction is also affected in this process. One has to emphasize that the mechanically processed ZnFe2O4 ferrite has an inverse spinel-like structure with a magnetic ordering temperature (above 40 K) higher than that of the equivalent bulk ferrite (11 K). On the other hand, it is shown in this work that the NiFe2O4nanocrysalline ferrite, prepared by sol-gel method, has no hysteresis loop shift effects, after field cooling protocol, and, at the same time, the hysteresis loops do not saturate. The apparent absence of horizontal loop shift effect (exchange bias) is explained by the fact that in the sol-gel method the crystalline grains are big (~19 nm) and consequently the exchange bias field goes to zero due to the fact that the HEBa 1/tFI, where the tFIparameter is the ferrimagnetic thickness assumed to be the grain size. Comparing the magnetic results obtained for the nanocrystalline NiFe2O4 ferrites prepared by high energy milling and sol-gel methods, it can be concluded that the hysteresis loop shifts are extremely dependent on the high magnetic anisotropy of the d-AFe2O4 (A = Ni and Zn) phase. Therefore, the loop shift effects are due the exchange bias field at the d-AFe2O4/n-AFe2O4 interfaces and also from the spin freezing effect caused by cooling the spin-glass-like phase under applied magnetic field.